Analisis Pengaruh Pemberdayaan Wanita Pedagang Sektor Informal Terhadap Peningkatan Pendapatan Rumah Tangga - Agung Yatiningrum; Joni Hendra; Saifullah Saifullah (Jurnal Manajemen dan Kewirausahaan, 2017)
The purpose of this study is to analyze the influence the women empowerment of informal sector traders related to factors (capital, number of working hours, number of labor, business location, effort experience, and level of education) to increasing of household income. The population in this study were female workers in informal trading business (business stalls) in the Leces Probolinggo District with a sample of 100 respondents.The data analysis uses multiple linear regression. The result of the analysis proves that the factors (capital, number of working hours, number of labor, business location, business experience, education level) have significant influence to the increasing of household income as simultan. The number of working hours has the dominant effect in increasing their income. If they want to increase their income, they should increase the number of working hours. While the capital and education level does not have a significant influence in increasing of household income   https://doi.org/10.26905/jmdk.v5i2.1588